Analisis Hukum Terhadap Eksistensi Sanksi A’massa Pada Delik Pidana Adat di Kabupaten Gowa - Raodatul Jannah; Syamsuddin Radjab; Bariek Ramdhani Pababbari (Alauddin Law Development Journal)
the problem of this study is how the existence of a'massa sanctions as a customary criminal offense in Gowaregency. how the existence of a'massa customary sanctions on criminal offenses in Gowa regency (case study of Tompobulu Sub-District), how the application of a'massa customary sanctions on criminal offenses is reviewed based on customary criminal law. Thetype of research is the type of Empirical Legal Research, found the existence of a'massa customary sanctions are still recognized by the community in Gowa kususnya district Tompobulu, a'massa customary sanctions is a manifestation of customary criminal law whose application is proven to be able to suppress the crime rate so this a'massa customary sanctions if in view of the general criminal, because of this a'massa sanction is still in practice but on the other hand the criminal code or positive law prohibits because it is considered a vigilante act